The use of mobile-assited language learning to enhance young adult EFL students' oral production - González González, Laura Leticia (2021)
The current research paper emphasizes the importance of enhancing oral skills in young adult EFL students. Nowadays, being able to communicate in English has become a must for many people. In Mexico, the need to speak English increases day by day (most jobs require people to do so). This study takes place at a school where English courses are based on a communicative approach, but even with that emphasis, students continue to have difficulties to communicate in the target language.